Claiming place : biracial young adults of the post-civil rights era - Kilson, Marion, 1936- (Bergin & Garvey, 2001)
Annotation Born on the crest of the Civil Rights Movement but coming-of-age at a time when biraciality was less widely acknowledged than it is at the opening of the new century, the participants in this project represent a transitional generation of Biracial Americans who share existential realities in a society dominated by White culture. These existential commonalties include ambiguous racial identities, color conundrums, and rejection by both people of color and European Americans. Nevertheless, biracial young adults'personal views and experiences are diverse.
Keywords: Multiracial people -- Race identity -- United States.; Multiracial people -- United States -- Social conditions -- 20th century.; Young adults -- United States -- Social conditions -- 20th century.; United States -- Race relations.; Jeunes adultes -- États-Unis -- Conditions sociales -- 20e siècle.; États-Unis -- Relations raciales.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Multiracial people -- Social conditions; Race relations; Multiracial people -- Race identity; Young adults -- Social conditions; United States; Interethnische Herkunft; Ethnische Beziehungen; USA; 1900-1999